Necesidades de formadores de formadores respecto a la inclusión de tecnologías digitales: Necesidades de formadores de formadores respecto a la inclusión de tecnologías digitales - Cabrera, Ana (2023)
The findings presented here are framed within the research called, PRAXIS 2: redesign of teacher training with digital technologies. This research was carried out in Uruguay in 2019 with the funding from the National Agency for Research and Innovation and the Education Training Council at the National Administration of Public Education. The methodological approach is defined as action research within the framework of learning and practice communities with teacher trainers. The work with the community includes three milestones: identification of practices (diagnosis and observation of classes including digital technologies), reflection and transformation of practices. This article aims at communicating the findings obtained from the needs expressed by the participants at the beginning of the work. It is concluded that it is relevant to diagnose the needs of teachers for the implementation of a “customized” training proposal.